Express as a single fraction in its simplest form (3)/(x+2) +  (4)/(x-3)

Answers

Answer 1
Answer: D:x+2\neq0\to x\neq-2\ and\ x-3\neq0\to x\neq3\n\n(3)/(x+2)+(4)/(x-3)=(3(x-3))/((x+2)(x-3))+(4(x+2))/((x+2)(x-3))=(3(x)+3(-3)+4(x)+4(2))/((x)(x)+(x)(-3)+(2)(x)+2(-3))\n\n=(3x-9+4x+8)/(x^2-3x+2x-6)=\boxed{(7x-1)/(x^2-x-6)}
Answer 2
Answer: (3)/(x + 2) + (4)/(x - 3) = (3(x - 3))/((x + 2)(x - 3)) + (4(x + 2))/((x + 2)(x - 3)) = (3x - 9)/(x^(2) - x - 6) + (4x+ 8)/(x^(2) - x - 6) =(7x -1)/(x^(2) - x - 6)

Related Questions

What is the value of the function at x=−2? y=−4 y equals negative 4 y = 0 y, = 0 y = 2 y = 2, y = 3
Bob travels from Inglewood to Anytown, a distance of 20kilometres, he walks 800 metres and bicylces the rest of the way. what percentage does he travel by bicylce?
Find the work done by a 25 N force applied for 6 meters.
The following function defines a recessive sequence:f(0) = -4f(1) = 12f(n) = -3•f(n -1) - 2•f(n - 2); for n > 1Which of the following sequences is defined by this recursive function?A) -4, 12, -28, 60, …B) -4, -12, -28, -60, …C) -4, 12, -18, 54, …D) -4, 12, -18, -54, …
Find the measure of angle X in the figure below Choices: 35°, 47°, 73°, 78°

Help me solve these problems please

Answers

Principal amount is $1510, so P = 1,510 dollars.

Compounding period is daily, so N = 365.

Interest rate is 12%, so r = 0.12

Time of investment is 3 years, so t = 3 years.

We can use compound interest formula as given below :-

Amount = P*(1+(r)/(N) )^((N*t))

Amount=1510*(1+(0.12)/(365) )^((365*3)) \n\n</p><p>Amount=1510*(1+0.000328767 )^((1095)) \n\n</p><p>Amount=1510*(1.000328767 )^((1095)) \n\n</p><p>Amount=1510*(1.433244609) \n\n</p><p>Amount=2164.199359 \approx 2164.20 \;dollars

Hence, total amount in account would be 2,164.20 dollars.

Please help me with this

Answers

Answer is 6 (D)

45 - 39 = 6
39 - 33 = 6
33 - 27 = 6

Answer:

A. - 6

Is the common difference

see the expressions below that prove so.

Step-by-step explanation:

The sequence shows -6 to each number is same as k-6 or even n-6

we use such letters to represent 1 value. Also the reason it is a negative number is because the numbers are decreasing within the sequence.

The nth expression is the first term equation shows -6n

and the number prior to 45 is  45+6 = 51

Put together this creates our nth term =   -6n + 51

The next term is where we use the common difference also.

next nth term =  (27) + (- 6) = 21   and so on proves it the 5th term

5th nth term = -6 x 5 +51 = 21

100th nth term = -6 x 100 +51 = -549

What are the coordinates of point B in the diagram?

Answers

4,-5 i am pretty sure hope this helps you 


Answer:

For plato, the correct option is B

Step-by-step explanation:

B.  (4, -5)

What's X?
Thank youuu

Answers

Answer:

35°

Step-by-step explanation:

Please see the attached picture for full solution.

Answer might be 35 degrees

Which of the following is x⁴ + y⁴ identically equal to?(A) (x² + y²)(x + y)(x - y)
(B) (x² + xy + y²)(x² - xy + y²)
(C) (x² + √2xy + y²)(x² - √2xy + y²)
(D) (x² + √3xy + y²)(x² - √3xy + y²)
(E) (x + y)²(x-y)²
Can someone explain me how to make it step by step?

Answers

x^4+y^4 \n \nx^4= (x^2)^2, y^4 = (y^2)^2 \n \nx^4- y^4= (x^2)^2 - (y^2)^2 = (x^2 + y^2)(x^2 - y^2 )\n \nnow \ you \ can \ factor \ the \ second \ again \n \n(hopefully \ you \ see \ that \ it's \ a \ difference \ of \ squares): \n \nx^4 - y^4= (x^2 + y^2)(x + y)(x - y) \n \nAnswer : \ (A) \ (x^2 + y^2)(x + y)(x - y) \n \n \n a^2-b^2 =(a-b)(a+b)

WILL MARK BRAINLIEST!!!!!!f(x) = x2 + 3; g(x) = Square root of quantity x minus two.

Find f(g(x)).

f(g(x)) = (x2 + 3)(Square root of quantity x minus two.)
f(g(x)) = Square root of quantity x minus two divided by quantity x squared plus three.
f(g(x)) = x + 1
f(g(x)) = Square root of quantity x squared plus three.

Answers

Answer:

The correct option is 3.

Step-by-step explanation:

The given functions are

f(x)=x^2+3

g(x)=√(x-2)

We need to find the value of f(g(x)).

f(g(x))=f(√(x-2))            [\because f(x)=x^2+3]          .... (1)

Substitute x=√(x-2) in function f(x) to find the value of f(√(x-2)).

f(√(x-2))=(√(x-2))^2+3

f(√(x-2))=x-2+3

f(√(x-2))=x+1

Substitute the value of f(√(x-2)) in equation (1).

f(g(x))=x+1

Therefore, the correct option is 3.

f(x) = x^2 + 3
g(x) = sqrt(x - 2)

f(g(x)) = x - 2 + 3 = x + 1